Peningkatan Modulus Elastisitas Tanah Lempung Menggunakan Presipitasi Kalsit yang Diinduksi Mikroba dan Terstimulasi Biostimulasi (MICP) - Fajri Hasan Nurrohman; Mahardi Kamalika Khusna Ali (Jurnal Pensil : Pendidikan Teknik Sipil, 2026)
Low-plasticity clay (CL) exhibits low stiffness and is easily deformable, thus requiring an efficient and environmentally friendly improvement method. Prior studies on Microbially Induced Calcite Precipitation (MICP) have predominantly emphasized improvements in soil compressive strength, whereas investigations addressing its effects on soil stiffness and elastic modulus remain relatively limited. Accordingly, the present study aims to evaluate the effectiveness of biostimulated MICP in enhancing the elastic modulus parameters (E₀ and Eₜ) of low-plasticity clay (CL). To achieve this objective, laboratory tests were conducted on soil specimens under two conditions, namely untreated samples and samples treated with an MICP solution, with incubation durations of 7 and 14 days. The Unconfined Compression Test (UCS) was conducted to obtain stress-strain relationships, which were then analyzed to determine the elastic modulus values. The results show that at 7 days of incubation, the MICP-treated soil exhibited increases of approximately 92% in E₀ and 90% in Eₜ compared to the untreated condition. With extended incubation to 14 days, the improvements became more pronounced, with E₀ increasing by approximately 104% and Eₜ by about 125% relative to untreated soil. The ANOVA results indicated that the differences between the untreated specimens and those treated with MICP were statistically significant, as evidenced by p-values below the 0.05 significance threshold. These findings demonstrate that the biostimulation process effectively enhances soil stiffness through interparticle calcite formation, providing a foundation for developing more efficient and eco-friendly soil stabilization methods applicable to infrastructure projects in tropical regions.